A strange dwarf scenario for the formation of the peculiar double white dwarf binary SDSS J125733.63+542850.5. Issue 1 (29th January 2018) - Jiang, Long; Chen, Wen-Cong; Li, Xiang-Dong
Abstract: The Hubble Space Telescope observation of the double white dwarf (WD) binary SDSS J125733.63+542850.5 reveals that the massive WD has a surface gravity log  g 1  ∼ 8.7 (which implies a mass of M 1  ∼ 1.06 M⊙ ) and an effective temperature T 1  ∼ 13 000 K, while the effective temperature of the low-mass WD ( M 2  < 0.24 M⊙ ) is T 2  ∼ 6400 K . Therefore, the massive and the low-mass WDs have a cooling age τ1  ∼ 1 Gyr and τ2 ≥ 5 Gyr, respectively. This is in contradiction with traditional binary evolution theory. In this paper, we propose a strange dwarf (SD) scenario to explain the formation of this double WD binary. We assume that the massive WD is a SD originating from a phase transition (PT) in a ∼1.1 M⊙ WD, which has experienced accretion and spin-down processes. Its high effective temperature could arise from the heating process during the PT. Our simulations suggest that the progenitor of SDSS J125733.63+542850.5 can be a binary system consisting of a 0.65 M⊙ WD and a 1.5 M⊙ main-sequence star in a 1.492 d orbit. Especially, the secondary star (i.e. the progenitor of the low-mass WD) is likely to have an ultra-low metallicity of Z  = 0.0001.